The type-2 peroxisomal targeting signal - Kunze, Markus (Biochimica et biophysica acta. Molecular cell research, 2020)
The type-2 peroxisomal targeting signal (PTS2) is one of two peptide motifs destining soluble proteins for peroxisomes. This signal acts as amphiphilic α-helix exposing the side chains of all conserved residues to the same side. PTS2 motifs are recognized by a bipartite protein complex consisting of the receptor PEX7 and a co-receptor. Cargo-loaded receptor complexes are translocated across the peroxisomal membrane by a transient pore and inside peroxisomes, cargo proteins are released and processed in many, but not all species. The components of the bipartite receptor are re-exported into the cytosol by a ubiquitin-mediated and ATP-driven export mechanism. Structurally, PTS2 motifs resemble other N-terminal targeting signals, whereas the functional relation to the second peroxisomal targeting signal (PTS1) is unclear. Although only a few PTS2-carrying proteins are known in humans, subjects lacking a functional import mechanism for these proteins suffer from the severe inherited disease rhizomelic chondrodysplasia punctata. •Two types of targeting signals, PTS1 and PTS2, destine proteins for peroxisomes.•PTS2 motifs are α-helical peptides recognized by a bipartite receptor complex.•PTS2 resembles other N-terminal targeting signals, but import mechanisms differ.•In humans, inactivation of PTS2-mediated import causes a severe inherited disease.